2016
DOI: 10.1002/jps.24661
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Organic Cation/Carnitine Transporter 1 and Multidrug Resistance-Associated Protein 1 Transport Activities With Protein Expression Levels in Primary Cultured Human Tracheal, Bronchial, and Alveolar Epithelial Cells

Abstract: Understanding how transporters contribute to the distribution of inhaled drugs in the lung is important for the discovery and development of such drugs. Protein expression levels may be useful to predict and understand drug distribution. As previously reported, organic cation/carnitine transporter 1 (OCTN1) and multidrug resistance-associated protein 1 (MRP1) have higher levels of protein expression among transporters in primary cultured human lung cells. Nevertheless, it is unclear to what extent transport ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…10e12 It has been reported that protein expression levels of organic cation/carnitine transporter 1 and mrp1 are well correlated with the transport activities in primary cultured human tracheal, bronchial, and alveolar epithelial cells. 13 But, on the other hand, we have found that mRNA expression levels of CYP enzymes, except for CYP3A4, are poorly correlated to metabolizing activity, and there is no correlation between mRNA and protein expression levels of transporters in human liver. 12 Therefore, simultaneous determination of the expression amounts of multiple proteins using QTAP methodology would be the most suitable approach to evaluate transport and metabolizing activities in the liver with high reliability and robustness.…”
Section: Introductionmentioning
confidence: 71%
“…10e12 It has been reported that protein expression levels of organic cation/carnitine transporter 1 and mrp1 are well correlated with the transport activities in primary cultured human tracheal, bronchial, and alveolar epithelial cells. 13 But, on the other hand, we have found that mRNA expression levels of CYP enzymes, except for CYP3A4, are poorly correlated to metabolizing activity, and there is no correlation between mRNA and protein expression levels of transporters in human liver. 12 Therefore, simultaneous determination of the expression amounts of multiple proteins using QTAP methodology would be the most suitable approach to evaluate transport and metabolizing activities in the liver with high reliability and robustness.…”
Section: Introductionmentioning
confidence: 71%
“…Quantitative targeted absolute proteomics (QTAP)-based protein quantification has enabled us to determine the absolute protein expression levels of transporters and metabolizing enzymes in the livers of humans and mice (Kamiie et al, 2008;Kawakami et al, 2011;Ohtsuki et al, 2011Ohtsuki et al, , 2012. Our previous analyses with QTAP have demonstrated the lack of correlation between mRNA and protein amounts of the plasma membrane transporters in human liver (Ohtsuki et al, 2012), but a good correlation was found between the protein amounts of organic cation/carnitine transporter 1 and MRP1 and their transport activities in primary cultured human respiratory epithelial cells (Sakamoto et al, 2016). Furthermore, most of the work on metabolic zonation has been done at the transcriptional level by using reverse transcription polymerase chain reaction and at the protein level by immunohistochemical analysis, in which there have been conflicting results, for example, regarding the regional expression of Mrp2 (Baier et al, 2006;Micuda et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At in vivo level, an impact of genetic polymorphism of OATP1B1 on the PK of its substrate, repaglinide, was accurately predicted using proteomics data 9 . Recently, Sakamoto et al also reported a significant correlation between the kinetic parameter V max for OCTN1 and MRP1 substrates with the protein expression in the plasma membrane of tracheal, bronchial, and alveolar cells 15,16 . While the above simplistic model to predict functional activity does not consider other catalytical factors such as cooperative binding for the drug substrate 25 and protein localization (for transporters) 11 , the above examples support the hypothesis that protein expression of both DMEs and transporters is one of the most critical predictors of variability in the functional activity.…”
Section: Quantitative Proteomics Data Can Be Used As a Critical Predimentioning
confidence: 93%